Comparing the prevalence, location, and severity of head and neck lymphedema after postoperative radiotherapy for oral cavity cancers and definitive chemoradiotherapy for oropharyngeal, laryngeal, and hypopharyngeal cancers. Issue 11 (31st July 2020) - Jeans, Claire; Brown, Bena; Ward, Elizabeth C.; Vertigan, Anne E.; Pigott, Amanda E.; Nixon, Jodie L.; Wratten, Chris
Abstract: Background: This study aimed to examine the prevalence, location, and severity of chronic internal, external, and combined head and neck lymphedema (HNL) in patients with head and neck (HNC) who were treated with definitive chemoradiotherapy (CRT) or postoperative radiotherapy (PORT). Methods: Sixty‐two participants between 1 and 3 years post‐treatment were recruited. Internal HNL was rated with Patterson's Scale. External HNL was graded with the MD Anderson Cancer Center Lymphedema Rating Scale. Results: Ninety‐eight percent of participants presented with some form of chronic HNL. Sixty‐one percent had internal HNL only, 35% had combined HNL, and 2% had external HNL only. Participants treated with PORT were more likely to experience combined HNL (69% vs 24%, P = .001), whereas those treated with CRT were more likely to have internal HNL only (74% vs 25%, P = .001). Conclusions: Chronic HNL is highly prevalent following multimodal treatment, and differences in HNL presentations exist between treatment modalities.